A Study of Building Brand by Driving-Market Behavior in Online Social Network - Wenjia, Liao (International Journal of Multidisciplinary in Management and Tourism, 2020)
Building brand is the need of a company strategy development. In the environment of online social network, There are four indicators contributing to build brand, including driving-market behavior, brand community, brand positioning and brand communication. It indicates that driving-market behavior can influence brand positioning and brand communication effectively and efficiently, especially for reversing existing customer preference, it changes the existing preferences of customers from a negative to a positive evaluation, marketers can apply the rule of reversing existing customer preference to influence the structure of the market and/or the behavior of market players (e.g., customers, competitors, and other stakeholders). Downloading Apps in the brand community has become a new trend in the time of IT, this design in the brand community can generate popularity from existing customers and latent customers, it contributes to brand communication. Brand community really can contribute to brand communication, but social capital, network effect, six degree of separation and viral loop can amplify the effect brand community has on brand communication. After mode study, I will implement case study of Xiao Mi brand, analyzing its competitive situation and showing that how its marketers operate brand marketing. I anticipate that firms need to manage both structure and behavior change, they often appear to move together in practice. My mode study proves that exceptional companies are able to manage the present through short-term, market-driven actions and, simultaneously, consider how to reshape markets by driving them into new competitive spaces. For the future research, I recommend that we should focus on “how much can market behavior be shaped?” , it is interesting to consider the extent to which market behavior can be shaped. The answer to this question may vary quite a bit by the industry involved, and it would be instructive to study variations across industries. In contrast, more traditional business-to-business markets may be less amenable to altering their behaviors.